1989
DOI: 10.1016/0014-5793(89)80791-4
|View full text |Cite
|
Sign up to set email alerts
|

CD3/T‐cell receptor coupling to a pertussis and cholera toxin‐insensitive G‐protein

Abstract: We have analyzed the effect of CD3/T-CeU receptor stimulation on GTP hydrolysis and GTP binding. We show that stimulation of Jurkat, T-cell, membranes with OKT3 results in a 50% increase in GTP hydrolysis which is specifically inhibited by GDP. Pretreatment of the membranes with neither pertussis toxin nor cholera toxin inhibited the GTP hydrolysis. We also show that stimulation with OKT3 increases the binding of GTP~,S to Jurkat membranes. These data strongly implicate the involvement of a G-protein in CD3/T-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In glial cells the positive effect of PKC activation can, however, be counteracted by an inhibitory effect of strong increases in intracellular calcium Fredholm 1992, 1993;Balmforth et al 1992). A similar effect is seen in lymphocytes (Fredholm et al 1987a;Nordstedt et al , 1989Kvanta et al 1989). In these cells it could be shown that the stimulatory effect of PKC activation predominantly occurs downstream of the receptor.…”
Section: A 2b Interactionsmentioning
confidence: 81%
“…In glial cells the positive effect of PKC activation can, however, be counteracted by an inhibitory effect of strong increases in intracellular calcium Fredholm 1992, 1993;Balmforth et al 1992). A similar effect is seen in lymphocytes (Fredholm et al 1987a;Nordstedt et al , 1989Kvanta et al 1989). In these cells it could be shown that the stimulatory effect of PKC activation predominantly occurs downstream of the receptor.…”
Section: A 2b Interactionsmentioning
confidence: 81%
“…Indirect evidences of Gprotein implication was brought forward by experiments showing a T-cell activating effect of GTP analogs [16] or fluoroaluminate ions [ 13,161. The use of bacterial toxins to explore the role of G-proteins in the activation of intact T-cells has led to somewhat conflicting results [13,[17][18][19][20]251, however the implication of G-proteins in various steps of T-cell activation has been more directly documented by cell-free experiments showing that triggering of CD3/TcR by specific antibodies [21], or IL-1 receptor occupancy [23,24], stimulate both GTP analogue binding and GTPase activity of membranes. Furthermore, membrane receptors for ConA have been shown to be physically linked to G-protein(s) able to stimulate a cytosolic phospholipase C in murine thymocytes [22].…”
Section: Discussionmentioning
confidence: 99%
“…been characterized (38,39). Gi(s) might be excluded as candidates for relaying CD3/TcR triggering, as they are recognized substrates for pertussis toxin and would not account for the lack of sensitivity of cell-activation to this toxin [21,38]. Gi might however transduce a cyclase-inhibiting signal issuing from Con A receptors [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This soluble tyrosine kinase shows considerable structural homologies with both p56'" and pp60c-8rc. It has been repeatedly demonstrated that T-cell activation leads to stimulation of GTPase activity, which might suggest the involvement of a G-protein [71]. However, this GTPase clearly differs from several of the classical heterotrimeric G-proteins, and it was very recently shown that T-cell activation leads to the stimulation of p21r"a [72].…”
Section: Receptor Interactions In Lymphocytesmentioning
confidence: 99%